Sustainable energy is in all of our interests - El-Katiri, L (Oxford Institute for Energy Studies, 2015)
The past few decades have witnessed a remarkable socio-economic development trajectory in the economies of the Middle East and North Africa (MENA). Despite glaring differences in income and political stability across MENA countries (including the proliferation of violence and political turmoil across parts of North Africa, the Levant, and Yemen over recent years) the region as a whole faces some very tough common challenges in the economic sphere, in the management of its natural capital: its energy and water resources. From the onset of the Middle East’s oil and later on its gas exporters’ stellar economic growth since the 1960s, fossil fuels have been intimately connected with the region’s rising wealth and socio-economic development that has enabled virtually universal access to both modern energy and treated fresh water across the MENA, and turned the Arab Gulf monarchies in particular into some of the wealthiest states in the world.